Operacionalizaç\~ao da Política de Garantia de Preços Mínimos para Produtos da Sociobiodiversidade 2009-2013: Há espaço para crescer - Jo\~ao Paulo Viana (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The Price-Support Policy for Biodiversity Derived Products (PGPMBIO) aims to reduce income variations for extractivists and to support the valorization of their products. In exchange, the extractivists, by using their traditional, reduced impact exploitation techniques, contribute to the conservation and sustainable use of natural resources inside and outside protected areas. The implementation of PGPMBIO is the responsibility of the National Supply Company (Conab), which sets a minimum price for selected products and operationalizes the payment of the benefit, in the form of a subsidy. The benefit corresponds to the difference between sale price of the extractive products and the minimum price set by the government. After four and a half years, the PGPMBIO has reached over 12 thousand extractivists in 11 states and 84 counties, paying R 16.1 million in subsidies. Extractivists from Bahia, Maranh\~ao and Amazonas received R 6.1 million (38%), R 4.7 million (29%) and R 2.2 million (14%), respectively. In the period under consideration, Conab allocated approximately R 64 million for payment of subsidies. Yet only 25% of this was actually paid out as subsidies for just six of the fourteen products supported by the policy. Approximately 38% of the amount paid was for piassaba fiber; followed by babassu seed (30%), rubber (27%) and Brazil nut (4%), complemented by assai and souari nut, which together accounted for less than 1% of payments. Upgrading PGPMBIO requires that Conab keeps expanding the portfolio of supported products as well as working together with partners in order to increase the number of DAP certified producers; and to adopt, in the calculation of minimum prices, the environmental costs of extractivists.
Keywords: Q57; 330; PGPMBIO; minimum prices; protected areas; traditional peoples; extractive products; non-timber products; biomes